Prevalence and Mortality of Post-traumatic Acute Kidney Injury in Children; a Systematic Review and Meta-analysis - Yousefifard, Mahmoud; Toloui, Amirmohammad; Forouzannia, Seyed Ali; Ataei, Neamatollah; Hossein, Hasti; Zareie Shab Khaneh, Amirali; Karimi Ghahfarokhi, Maryam; Jones, Michael E.; Hosseini, Mostafa (Archives of Academic Emergency Medicine, 2022)
Introduction: Numerous studies on acute kidney injury (AKI) following trauma have been performed, and acceptable findings have been reported in the adult population. The present meta-analysis summarizes the studies performed on the pediatric population to evaluate the prevalence of AKI following trauma in this population. Method: The Medline, Embase, Scopus and Web of Sciences databases were searched for articles published until the July, 31, 2021. Two independent reviewers screened observational studies performed on children with physical trauma and AKI related to it. The interested outcomes were the prevalence and mortality of trauma-related AKI in traumatized children. Results: Data of 9 articles were included in the present meta-analysis. The prevalence of trauma-related AKI varied between 0% and 30.30% among included studies. Pooled analysis showed that the prevalence of trauma-related AKI was 9.86% (95% CI: 8.02 to 11.84%). The prevalence of AKI after exertional rhabdomyolysis, direct physical trauma, and earthquake related injuries was 0%, 12.64% and 24.60%, respectively. There was a significant relationship between the prevalence of AKI and trauma etiology (p = 0.038). Moreover, the occurrence of AKI in children with trauma was associated with an increased risk of mortality (OR = 5.55; 95% CI: 2.14 to 13.93). Conclusion: The findings of the present study showed that 9.86% of children develop AKI following trauma, which may increase their risk of death by about 5.5 times. Nevertheless, since none of the studies had adjusted their analyzes for potential confounders, caution should be exercised in interpreting the relationship between trauma-related AKI and mortality.